Case Report and Clinical Reasoning: Fulminant Liver Failure and Invasive Aspergillosis Following Ocrelizumab Treatment in a 21 Year-Old Woman. (January 2023) - McEntire, Caleb R. S.; Lesser, Cammie F.; Venna, Nagagopal
We present the case of a 21 year-old woman with newly diagnosed relapsing-remitting multiple sclerosis who is given a single dose of ocrelizumab and placed on moderate-dose steroids with subsequent development of hepatic failure who goes on to develop highly fulminant systemic and central nervous system (CNS) aspergillosis. Ocrelizumab has no documented association with aspergillus infection, and moderate-dose steroids less often lead to such fulminant disease, but liver failure is associated with often-fatal aspergillus infection. We emphasize that liver failure is an underrecognized immune dysregulated state that predisposes to bacterial and fungal infections and suggest changes in diagnostic reasoning that could be considered in patients with multiple modalities of immunosuppression.